A study on the normative path of ethics review in China: based on the perspective of Panopticism - Wu, Leqian; Kong, Xiangjin (Frontiers in Medicine, 2023)
Modern biomedical technology is in an era of dramatic development, which brings unprecedented challenges to the work of ethics review and provides a turning point for the construction of ethics review system. The current ethics review committee (ERC) in China is executed with low efficiency and quality, which can hardly meet the current needs of biomedical research involving human beings. This paper summarizes the main connotations and roles of the sign system technique and the discipline mechanism through the idea of Foucault’s Panopticism, and proposes to incorporate the Panopticism into the construction of the ethics review system and establish the sign system and discipline mechanism of ethics review, in order to build an ethics review system and the operation system of the ethics review committee suitable for China’s national conditions.